Ballistic and electromagnetic shielding behaviour of multifunctional Kevlar fiber reinforced epoxy composites modified by carbon nanotubes. (August 2016) - Micheli, D.; Vricella, A.; Pastore, R.; Delfini, A.; Giusti, A.; Albano, M.; Marchetti, M.; Moglie, F.; Primiani, V. Mariani
Abstract: Overall goal of the research is to develop a material simultaneously able to absorb mechanical shocks and shield from electromagnetic interferences. Several layered composite materials aimed at such multi-functionality have been conceived and realized: the characterization has been carried out in terms of electromagnetic shielding effectiveness in the range 0.8–8.0 GHz and of energy absorbing capability upon impact of metallic bullets fired at about 400 m/s and 1000 m/s (such velocity allows to explore the low energy range of potential mechanical shocks in aerospace structures). The composite specimens under test are ∼3.5 mm thick tiles made of hybrid multi-scale material: the manufacturing has been performed by integrating several layers of Kevlar fabric and carbon fiber plies within a polymeric matrix reinforced by carbon nanotubes. The electromagnetic shielding effectiveness has been measured by means of a reverberation chamber; the performances of the layered composites approach the metallic behavior with values of shielding up to 80 dB. The impact tests have been carried out by using an in-house built linear electromagnetic accelerator, known as railgun; the results show that a thin and light tile of the designed composite material is able to absorb high energy impacts with local delamination of the layered structure.